Forensic-Psychiatric Risk Evaluations: Perspectives of Forensic Psychiatric Experts and Older Incarcerated Persons From Switzerland - Wangmo, Tenzin; Seaward, Helene; Pageau, Felix; Hiersemenzel, Lutz-Peter; Elger, Bernice S. (Frontiers in Psychiatry, 2021)
Background: Forensic-psychiatric risk assessments of persons in prisons aim to provide treatment for their mental health disorders to prevent risk of recidivism. Based on the outcomes of such evaluations, it is decided, for instance, whether the person can be released or be assigned to further treatment with or without privileges. A negative evaluation would mean that the assessed person must remain in prison or in a forensic institution until his or her mental health has improved to live safely in the community. This paper highlights the process of forensic-psychiatric evaluations and the challenges faced by the two parties directly involved in this process in Switzerland. Methods: Data for this manuscript are gathered using semi-structured one-to-one interviews. The study participants included a purposive sample of 41 older incarcerated persons under measures, and 23 expert participants working in Swiss prisons or forensic institutions. We analysed data using thematic analysis. Results: Study findings within four themes are reported. First we describe the standards and procedures that expert participants use to carry out adequate risk assessments and conditions under which they refuse to perform such assessments. Thereafter, we present expert participants’ concerns associated with predictive risk assessments and highlight the need to be cautious in drawing conclusion from them. We then reveal older incarcerated participants’ reports on the inconsistencies with the forensic expertise and their belief that these reports tend to be negative towards them. The final theme concerns older participants’ experiences of how these evaluations negatively impact their lives and their perspectives of a different future. Conclusion: The study findings about forensic-psychiatric risk assessments point to the need for a clearer communication on how these evaluations take place and how decisions are taken based on them. As incarceration under measures denotes the necessity to continue therapy and reduce dangerousness, it is important that accused person understands his or her real progress, feel that the decisions are objective and justified, and are aware of the progress needed to achieve the goal of eventual release. Such clarity will not only be valuable for those under measures, but also the justice system.